2013
DOI: 10.1177/0047287513506290
|View full text |Cite
|
Sign up to set email alerts
|

Seniors’ Travel Constraints and Their Coping Strategies

Abstract: This article utilized content analysis of seniors' narratives on the Internet to uncover the central themes related to their perceptions of travel constraints and the ways through which seniors negotiate such barriers. The study results suggest that aging is associated with alterations in the order of salient constraints proposed by the hierarchy of leisure constraints theory, which in turn affect seniors' preferences for "safe" options such as packaged tours. Using gerontology and decisionmaking theories, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(109 citation statements)
references
References 54 publications
3
95
0
5
Order By: Relevance
“…This might be reflected by their experiences and knowledge collected since they were young until becoming a seniority. Many scholars (e.g., Long, 1998;Moschis, 1996;Ahmad, 2002Ahmad, , 2003Kazaminia, Del Chiappa, & Jafari, 2015;Datillo et al, 2015) in the general consumer behaviour literature have reported that the older consumer market has become more heterogeneous than the younger consumers in terms of preferences, motives, and spending power. They also tend to be more discerning and will demand higher quality service during travelling, as well as a greater degree of choice and flexibility in their travel and tourism consumption.…”
Section: Characteristics Of the Senior Tourism Market 221 Travel Momentioning
confidence: 99%
“…This might be reflected by their experiences and knowledge collected since they were young until becoming a seniority. Many scholars (e.g., Long, 1998;Moschis, 1996;Ahmad, 2002Ahmad, , 2003Kazaminia, Del Chiappa, & Jafari, 2015;Datillo et al, 2015) in the general consumer behaviour literature have reported that the older consumer market has become more heterogeneous than the younger consumers in terms of preferences, motives, and spending power. They also tend to be more discerning and will demand higher quality service during travelling, as well as a greater degree of choice and flexibility in their travel and tourism consumption.…”
Section: Characteristics Of the Senior Tourism Market 221 Travel Momentioning
confidence: 99%
“…The WTO estimates that by 2050 the population aged 60 and older will represent more than 2 billion international trips, a vastly greater number if we compare it to the resulting 593 million for the year 1999 (Patterson, 2006). Chen and Shoemaker (2014), Chu and Chu (2013), Cooper et al (2007), Glover and Prideaux (2009), Kim and Jang (2015), Mahadevan (2014) and Ryan (1995) point to the aging baby boom generation, with a more leisurely and recreational travel lifestyle than any other generation has ever had and great purchasing power (Dann, 2007;Kazeminia et al, 2015;Kuo and Lu, 2013;Van den Berg et al, 2011), as one of the most important markets for the tourism industry.…”
Section: Introductionmentioning
confidence: 99%
“…They often travel, compared with young people, they spend more time on vacation and spend more on leisure activities. [3] …”
Section: The Analysis Of the Present Situation Of The Elderlymentioning
confidence: 99%